THREE DELUSIONAL IDEAS OF THE WESTERN WORLD ON NATURAL ENVIRONMENT, HUMANS, AND THEIR SOCIETIES - M. Becker, Ralph (Universidade Federal de Pernambuco, 2016)
With the globalization in the late 20th century, the expansion of Western tradition enters into a new phase of its history, causing severe consequences not only for the Western industrial nation, but also for all human societies. Environmental problems, the mechanizing of our daily life, and the enormous pressure on national economic systems within the world market, are phenomena that not only affect the diversity of world cultures and societies, but also the future of our planet. This essay tries to trace back the origin of essential thought patterns of the Western world. The essay commenced by presenting ideas about key elements of human existence of some extraordinarily influential Western philosophers, which justified norms of behavior passed through successive generations and which have become subconscious constituent part of social behavior. These ideas concern the human relationship to nature, the importance of individualism, and the belief in unlimited growth of economic systems. These ideas are contrasted by anthropological examples presenting alternative attitudes of non-Western societies regarding their relationship to nature, society, and ethics.